Interactive Learning Media Local Culture Based for Teaching Reading: Students’ Reading Comprehension and Perception - Tio Uli; Indah Tri Purwanti; Jismulatif (Universitas Islam Negeri Palopo, 2025)
The integration of digital tools and cultural content has been explored in every level of education, yet there are still few studies that have connected it to Riau local wisdom, particularly its tourism destination. This research aimed to develop an interactive learning media based on Riau tourism places for learning descriptive text. This research followed the ADDIE model by Branch (2009) for its developmental process, involving students’ need analysis, developing the prototype, and evaluation. There were two schools involved in this study as the participants. One private school served as the small evaluation group, and one public school served as the field test. The data were collected using a questionnaire, a reading comprehension test, and an interview. The data were analyzed using qualitative and quantitative approach. This research found that the media was valid and practical due to the average score obtained from the experts’ validation and small evaluation group of 4.02 and 3.29, respectively. Furthermore, it also had a potential effect on students’ reading proficiency in the field test implementation. The experiment group obtained 55.59 for the pre-test, and after implementing the media in the classroom, the score improved to 74.00 for the post-test. The students gave positive feedback as well on the employment of the media in the classroom. This showed that digital media, as an innovative media, could be one of the strategies that should be employed in English reading classes for senior high school students to enhance students’ reading comprehension, contribute positive perception, and promote local tourist sites.